DEVELOPMENT OF DRIVING GUIDANCE SYSTEM FOR AUTOMOBILE DRIVER - Chandrakant K Vhare1 Arati Lale2 Dhanashree Sonawane3 Gayatri Joshi4 Namrata Parvat5 Sanjay Kulal6 (International Journal of Innovations in Engineering Research and Technology, 2022)
The speed changing mechanism is quite different as if the new learner/driver are faces lots of problem while changing the gear and adapting the vehicle speed according to that so our aim is to simplify this process.Also changing gears while changing speed according to road and traffic condition may get hectic and confusion may occur confusion in such time may lead to accidents so to avoid that thus system is useful.According to statistics 60% of total road accidents are due to stressful conditions of new learners so to build up confidence and provide a smart solution on time is our main objective. It also been seen that due to situations like pandemic it was not possible to give actual on road training new drivers so we tried virtual training which resulted in lack of confidence to face reality but this system may prove effective in such a cases too.